2007
DOI: 10.2166/wst.2007.478
|View full text |Cite
|
Sign up to set email alerts
|

Winery wastewater treatment by constructed wetlands and the use of treated wastewater for cash crop production

Abstract: A 45 m long, 4 m wide and 1 m deep wetland was constructed at Goudini in 2002 to treat distillery and winery effluent. After the plants were fully established, the wastewater with an average chemical oxygen demand (COD) of 14,000 mg/l was introduced to the wetland system at a rate of 4,050 litres per day. After treatment, wastewater at the outlet had an average COD of 500 mg/ l, indicating more than 90% COD removal. After treatment, the wastewater was used to irrigate cash crops as part of poverty alleviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The data obtained in this study compare well with the data presented by Mulidzi (2006), who used a constructed wetland to treat winery and low-strength distillery waste. An average annual COD removal of 80 to 83% was obtained with a hydraulic retention time of 14 days.…”
Section: Figuresupporting
confidence: 82%
See 1 more Smart Citation
“…The data obtained in this study compare well with the data presented by Mulidzi (2006), who used a constructed wetland to treat winery and low-strength distillery waste. An average annual COD removal of 80 to 83% was obtained with a hydraulic retention time of 14 days.…”
Section: Figuresupporting
confidence: 82%
“…Although the hydraulic retention time was fairly long, constructed wetlands do offer the advantage of being a relatively low-maintenance technology once established, and therefore low cost if the land is available. The treated wastewater in Mulidzi's (2006) study was shown suitable for use for irrigation and used to produce a cash crop in the form of cabbages. However, biological processes are not the only mechanism that can be utilised for winery wastewater remediation.…”
Section: Figurementioning
confidence: 94%
“…The majority of the literature reports on CWs at wineries in areas with temperate or arid climates, for example, California Grismer et al, 2001Grismer et al, , 2003, Italy (Masi et al, 2002), Spain (Mena et al, 2009;Serrano et al, 2011;de la Varga et al, 2013) and South Africa (Mulidzi, 2007(Mulidzi, , 2010. However, the use of CWs at wineries in cooler, continental climates in active viticulture regions such as southern Ontario, Canada, has received little attention, even though there are ∼20 to 30 in use in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In California there are examples of wineries reusing treated WW for landscaping and frost protection (Hamilton et al, 2007), and several case studies of wastewater characterization and treatment for reuse have been published, including research conducted in Australia (Christen et al, 2010;Laurenson et al, 2012), Spain (Bustamante et al, 2005), South Africa (Mulidzi, 2007), and Mexico (Mendoza-Espinosa et al, 2008). A recent study compared the effects of solutions, ranging in SAR and PAR from 5 to 40, on a predominantly montmorillonite Australian vineyard soil (Arienzo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%